Basic Quran recitation multimedia application for Malay-speaking readers based on meaningful learning approach: Analysis and design - Azman, Farah Nadia; Dolhalit, Mohamad Lutfi; Salam, Sazilah (2011)
In recent years, much research has been devoted to the usage of ICT in the integration between multimedia technology and education. Exploration on effective incorporation of interactive courseware in teaching and learning has garnered high interest from both educationists and computer science scholars worldwide in the last several years. However, the implications of basic Quran script multimedia learning have been less pervasive with difficulties resulted by language barrier of Arabic word pronunciation faced by Malay- speaking audience. This research proposes a framework for the development of Quran script learning multimedia application which suggests solutions to the stated problem. In this paper, we verify the general understanding of Arabic alphabet, which embodies the important principles of meaningful learning. In order to fulfill this purpose, we demonstrate that powerful computer based instruction with the acclaimed meaningful learning could deliver immediate impact towards Quran reading skills.